Customization of e-textile sensory tools for people with dementia. (2nd January 2022) - Tan, Jeanne; Chen, Amy; Shao, Li; Kim, Heeyoung; Ge, Lan
Abstract: Sensory activities are used to increase social engagement for people with dementia, who may struggle to participate in activities due to deteriorating cognitive functions. Sensory tools are used but these can be inappropriate since they are not designed for people with dementia. This paper details the design of an e-textile sensory tool for people with dementia, with stakeholders in Mainland China. The concept, a sensory wall, was derived from a previous co-design project in Hong Kong. However, the design context differs, and this work highlights barriers to implementing co-design in sensory tool design. Instead, this project took a collaborative customization approach. This paper describes the design processes and evaluations for the first and second sensory wall, with context on dementia care in Mainland China. This paper highlights considerations in the design of a sensory tool for people with dementia, and the benefits of stakeholder engagement in sensory tool design.